On the Compatibility of Fish Meal Replacements in Aquafeeds for Rainbow Trout. A Combined Metabolomic, Proteomic and Histological Study - Palomba, Antonio; Melis, Riccardo; Biosa, Grazia; Braca, Angela; Pisanu, Salvatore; Ghisaura, Stefania; Caimi, Christian; Biasato, Ilaria; Oddon, Sara Bellezza; Gasco, Laura; Terova, Genciana; Moroni, Federico; et al. (Frontiers in Physiology, 2022)
The sustainable development of modern aquaculture must rely on a significant reduction of the fish meal (FM) used in aquafeed formulations. However, FM substitution with alternative ingredients in diets for carnivorous fish species often showed reduced nutrient absorption, significantly perturbed metabolisms, and histological changes at both hepatic and intestinal levels. In the present study, rainbow trout (Oncorhynchus mykiss) were fed three different experimental aquafeeds. A control diet with higher FM content (27.3%) than two test formulations in which FM was substituted with two more sustainable and promising alternatives: insect meal (Hermetia illucens larvae = 10.1%, FM = 11.6%) and poultry by-products meal (PBM = 14.8%; FM = 11.7%). Combined metabolomics and proteomics analyses of fish liver, together with histological examination of liver and intestine demonstrated that a well-balanced formulation of nutrients in the three diets allowed high metabolic compatibility of either substitution, paving the way for a deeper understanding of the impact of novel raw materials for the fish feed industry. Results show that the main metabolic pathways of nutrient absorption and catabolism were essentially unaltered by alternative feed ingredients, and also histological alterations were negligible. It is demonstrated that the substitution of FM with sustainable alternatives does not have a negative impact on fish metabolism, as long as the nutritional requirements of rainbow trout are fulfilled.